Habitat Integrity in Protected Areas Threatened by LULC Changes and Fragmentation: A Case Study in Tehran Province, Iran - Parvaneh Sobhani; Hassan Esmaeilzadeh; Shahindokht Barghjelveh; Seyed Mohammad Moein Sadeghi; Marina Viorela Marcu (Land, 2021)
The integration and connection of habitats in protected areas (PAs) are essential for the survival of plant and animal species and attaining sustainable development. Investigating the integrity of PAs can be useful in developing connections among patches and decreasing the fragmentation of a habitat. The current study has analyzed spatial and temporal changes to habitat to quantify fragmentation and structural destruction in PAs in Tehran Province, Iran. To achieve this purpose, the trends in land use/land cover (LULC) changes and the quantitative metrics of the landscape ecology approach have been examined. The results revealed that in Lar National Park, low-density pasture has the top increasing trend with 4.2% from 1989 to 2019; in Jajrud PA, built-up has the top increasing trend with 1.5% during the studied years; and among the land uses in TangehVashi Natural Monument, bare land has the top increasing trend with 0.6% from 1989 to 2019. According to the findings, habitat fragmentation and patch numbers have expanded in the studied areas due to the development of economic and physical activities. The results also indicate that the current trend of habitat fragmentation in PAs will have the highest negative impacts, especially in decreasing habitat integrity, changing the structure of patterns and spatial elements, and increasing the edge effect of patches.